Analysis of Smoking Habits to Community Attitudes and Behavior Intention Concerning No-Smoking Area (KTR) - Muttaqin, Nyta Ellisa; Bastian, Ardi (Universitas STRADA Indonesia, 2020)
Kediri Regency has made a joint commitment to the establishment of a no-smoking area (KTR) in 2019. No Smoking Area (KTR) is set in the Joint Regulation of the Minister of Health and Minister of Home Affairs No. 188/Menkes/Pb/I/2011, No. 7 of 2011 on Guidelines for Non-smoking Areas. The purpose of this study was to analyze the influence of smoking habits on the attitudes and behavioral intentions of the community towards a No Smoking Area if applied in Kanigoro Village, Kras District, Kediri Regency. The research methodology used in this research is the method quantitative. This research using design cross-sectional. The population in this study is the Kanigoro village community, Kras District, Kediri Regency with a total sample of 237 respondents. Statistical tests used in data analys is of the research is linear regression test simple with degrees trust = 0.05. The results showed that there was an influence of smoking habits on people's attitudes about a non-smoking area in Kanigoro Village, Kras District, Kediri Regency with a significance value of 0.023. Besides that of there search also found that there is no influence smoking habit to behavior intention to the community concerning the region without cigarette in the village Kanigoro Kras District Kediri Regency with the significance of 0,250. The community of Kanigoro Village, Kras District, Kediri Regency give positive attitude about the plan to implement KTR in their area, this shows their full support for the government to implement KTR in the area.